2015
DOI: 10.1007/s00417-015-2939-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the difficulty of graft unfolding and attachment on the outcome in descemet membrane endothelial keratoplasty

Abstract: There is no correlation between corneal donor tissue characteristics and the degree of difficulty of unfolding using graft lamella older than 49 years. Therefore, it is not possible to select grafts best suited for DMEK surgery on the basis of donor characteristics when the donor age is above 50 years. Preoperative visual acuity influences the grade of difficulty. The rate of graft detachments and endothelial cell loss increases significantly with a more difficult graft unfolding. The proposed grading system m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 16 publications
5
56
1
1
Order By: Relevance
“…Difficulties in unfolding the graft may increase the amount of manipulation needed, leading to subsequent graft damage and potential increased risk of detachment (Maier et al. ). Given that the DSEK grafts were transplanted in an oedematous (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in unfolding the graft may increase the amount of manipulation needed, leading to subsequent graft damage and potential increased risk of detachment (Maier et al. ). Given that the DSEK grafts were transplanted in an oedematous (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of this step is important as it has been reported that the rate of graft detachments and EC loss increases significantly with a more difficult graft unfolding, probably related to greater endothelial trauma 55. The use of longer-acting gas (most commonly, non-expansile concentrations of SF 6 gas with air, ie, 20% SF 6 ) intraoperatively with a peripheral iridectomy has been described with no increased toxicity to corneal endothelium, but this has not been directly compared with the use of air in a randomised fashion to demonstrate that this actually improves graft adhesion 44.…”
Section: Surgical Techniques: Donor Insertionmentioning
confidence: 99%
“…Initial reports of complete graft detachments were as high as 30%,4 while partial graft detachments were up to 62–63% 17 19. However, with improved techniques and surgical experience, reported graft detachments have reduced to 34.6% in a multicentre study,55 and as low as 4% in one case series 56. However, when evaluating DMEK complications one has to be aware that some authors choose to emphasise on re-bubble rates rather than detachment rates.…”
Section: Complications and Postoperative Managementmentioning
confidence: 99%
“…It has been shown that increased difficulty in unfolding the graft in the anterior chamber leads to higher postoperative endothelial cell loss 13 ; we speculate that the same may be true for difficulties during graft preparation. Although endothelial cell loss after preparation seems to be slightly reduced when using the novel instrument, this result is not statistically significant.…”
Section: Discussionmentioning
confidence: 65%